Improvement of directions for increasing the quality and efficiency of inclusive education in higher education institutions - Nutfiyeva Dildora (Genius Publishing Group, 2023)
Inclusive education is a process that involves the transformation of schools and other centers of learning so to cater for all children—including boys and girls, students from ethnic minorities, those affected by HIV and AIDS, and those with disabilities and learning difficulties. Education takes place in many contexts, both formal and non-formal, and within families and the wider community. Consequently, inclusive education is not a marginal issue, but is central to the achievement of high-quality education for all learners and the development of more inclusive societies.
Keywords: integration; inclusion; development; services and institutions.